Students' Misconceptions about Force Concepts and Intervention Strategies in Elementary School - Mahfudhotin Miratul; Mahfudhotin Nisa; Mir Atul Ilmiyah; Nur Haningtyas Agustin (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2026)
Natural Science learning in elementary schools is intended to develop students’ accurate understanding of scientific concepts. However, misconceptions regarding the concept of force are still commonly encountered. This study aims to examine the forms of students’ misconceptions, identify the factors contributing to them, and describe the strategies employed to address these issues at SDN Sukolilo II Tuban. A qualitative approach with a descriptive case study design was adopted. The participants consisted of one fourth-grade teacher and 31 fourth-grade students. Data were collected through interviews, observations, and documentation and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that force concepts were taught using a contextual approach by relating them to students’ everyday experiences. Nevertheless, several misconceptions persisted, including the belief that force only involves pushing or pulling moving objects and limited understanding of how force affects an object’s motion and shape. These misconceptions were associated with the oversimplified and incomplete presentation of concepts in the Student Worksheets. To overcome these problems, teachers reinforced the material by utilizing various learning resources, providing more contextual explanations, and incorporating real-life examples, thereby helping students develop a more accurate understanding of scientific concepts.